Characteristics of Ethnic Identity Among Students - Safarova Elshad, Jamila (2020)
The paper shows the characteristics that influence the ethnic identity of students educated in the Azerbaijani and Russian languages.The thoughts related to the study about  ethnic identity within the studies conducted in this way, as well as the psychological features of this process in youthful individuals are analyzed.Analysis of the results demonstrates that learners, studying in Azerbaijani department have indicators of the cognitive element of the ethnic identity higher than those of the learners studying in Russian department. This means that the level of self-awareness of their belonging to this ethnic group, opinions about the features of their own ethnic group are higher among students of the Azerbaijani Department. Analysis of the results also reveals the fact that students, studying in Azerbaijani language have indicators of the affective component of ethnic identity higher than students studying in Russian language. This considers a positive attitude towards their ethnos as a group, as well as the fact that young people have a definite emotional feel of acceptance to their ethnic group, a high sensitivity towards their ethnos.